Implikasi environmental, social, and governance (esg) terhadap kinerja perbankan syariah di indonesia - Yatimi, Muh Asrul (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the implications of ESG on banking performance in Indonesia. The results indicate that the implementation of ESG can improve the financial performance and reputation of Islamic banks, as well as help reduce operational risks and build stronger relationships with the community. Despite challenges in measuring and maintaining consistent ESG standards, Islamic banks have a significant opportunity to lead in sustainable financial practices. With increasing awareness of sustainability, the implementation of ESG can attract more investors and expand the customer base. Research shows that sound ESG disclosure positively impacts financial performance and attracts investors concerned with sustainability. However, ESG implementation in Islamic banking still faces several challenges, such as a lack of clear standards and limited measurable data. However, with growing awareness of the importance of sustainability, Islamic banks in Indonesia have the opportunity to lead in sustainable finance practices and make positive contributions to society and the environment.